2009
DOI: 10.1089/dia.2008.0024
|View full text |Cite
|
Sign up to set email alerts
|

Dual Radiotracer Analysis of Cholinergic Neuronal Changes in Prediabetic Mouse Pancreas

Abstract: Background: Pancreatic neuronal changes associated with beta cell loss in type 1 diabetes mellitus are complex, involving, in part, parasympathetic mechanisms to compensate for preclinical hyperglycemia. The parasympathetic neurotransmitter acetylcholine (ACh) mediates insulin release via M3 muscarinic receptors on islet beta cells. The vesicular ACh transporter (VAChT) receptor has been shown to be a useful marker of cholinergic activity in vivo. The positron emission tomography (PET) radiotracer (ϩ)-4-[ 18 F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 25 publications
(32 reference statements)
0
3
0
Order By: Relevance
“…[ 18 F]FBT was synthesized as previously described. 14,17 Approximately 5 mCi of [ 18 F]FBT was injected intravenously into each subject. Each PET scan was acquired in a dynamic fashion from time of injection through 90 min post-injection.…”
Section: Methodsmentioning
confidence: 99%
“…[ 18 F]FBT was synthesized as previously described. 14,17 Approximately 5 mCi of [ 18 F]FBT was injected intravenously into each subject. Each PET scan was acquired in a dynamic fashion from time of injection through 90 min post-injection.…”
Section: Methodsmentioning
confidence: 99%
“…18 F-FBT was further used as a tool to investigate glucose tolerance in adult female monkeys [153]. Considering the reduced cholinergic innervation in T1DM and the role of the parasympathetic neurotransmitter ACh in insulin production, Clark and co-authors further tested the feasibility of dual radiotracer analysis in identifying neurofunctional changes in T1DM using 18 F-FBT and 4-3 H-DAMP, with the former probe targeting VAChT and the latter probe binding to M3 muscarinic receptors on β-cells [154]. The authors found that the combined use of these two tracers may efficiently assess insulin production ability, indicating that noninvasive synergistic imaging of pancreatic cholinergic activity and M3 muscarinic receptor density may be an effective method for evaluating BCM and β-cell function.…”
Section: Vacht Targeting Probementioning
confidence: 99%
“…Clark et al, using 18 F-4-fluorobenzyltrozamicol, imaged vesicular acetylcholine transporters on presynaptic neuronal vesicles innervating the pancreas, showing increased 18 F-4-fluorobenzyltrozamicol up-take in prediabetic rodent pancreata (9). …”
Section: Search For Biomarkers Of β-Cellsmentioning
confidence: 99%